Geospatial analysis of end-stage renal disease among patients attending hemodialysis units in Alexandria, Egypt - Reham A. EL-Hofy; Safia I. Shehata; Azza F. Abou EL-Naga; Mohamed H. Bahnassy; Gihan I. Gewaifel; Nahla A. Gamaleldin (Journal of the Arab Society for Medical Research)
Background/aim End-stage renal disease (ESRD) is increasing worldwide and renal replacement therapy is inevitable to prevent death. Geographic information system (GIS) analysis is particularly suitable for chronic kidney disease (CKD) and ESRD. Spatial analysis is an important tool for better decision-making and planning. The aim of this study was to utilize geospatial analysis of ESRD in Alexandria for understanding the interplay between geography and other risk factors and for guiding resource allocation. Patients and methods A cross-sectional study was adopted, 950 ESRD patients were interviewed during the period from November 2021 to December 2022. Data were collected using predesigned structured interview questionnaire, which included sociodemographic information and the patient’s medical history. This information was then used for the development of the spatial representation of data and cluster analysis for ESRD patients attending hemodialysis units in the districts of Alexandria governorate. Results The results of the study showed that the mean age of ESRD patients (n=950) was 49±16.2 years. 538 of studied patients (56.6%) were males. Hypertension was the most frequent main etiology of ESRD (31.3%). It was found that 100–150 hypertensive patients were in Al-Ameria and Sharq district. Moreover, greater than 150 hypertensive patients were in Al-Muntazah district. Although Al-Muntazah district had the highest number of ESRD cases (no.= 247), it was not a significant cluster (P= 0.15). On the other hand, Al-Ameria district had a significant cluster of ESRD cases (no.= 177, P= 0.002). Conclusion It is recommended to target future screening programs and awareness campaigns in Almeria district to raise public awareness about early detection and prevention of chronic kidney disease this will help to prevent further progression to ESRD. Further studies are required to assess the accessibility to renal dialysis units in Egypt.